Differential ability of MSCs isolated from placenta and cord as feeders for supporting ex vivo expansion of umbilical cord blood derived CD34(+) cells - Kadekar, Darshana (Stem Cell Res Ther, 2015)
INTRODUCTION: Ex vivo expansion of umbilical cord blood (UCB) is attempted to increase cell numbers to overcome the limitation of cell dose. Presently, suspension cultures or feeder mediated co-cultures are performed for expansion of hematopoietic stem cells (HSCs). Mesenchymal stem cells (MSCs) have proved to be efficient feeders for the maintenance of HSCs. Here, we have established MSCs-HSCs co-culture system with MSCs isolated from less invasive and ethically acceptable sources like umbilical cord tissue (C-MSCs) and placenta (P-MSCs). MSCs derived from these tissues are often compared with bone marrow derived MSCs (BM-MSCs) which are considered as a gold standard. However, so far none of the studies have directly compared C-MSCs with P-MSCs as feeders for ex vivo expansion of HSCs. Thus, we for the first time performed a systematic comparison of hematopoietic supportive capability of C and P-MSCs using paired samples. METHODS: UCB-derived CD34(+) cells were isolated and co-cultured on irradiated C and P-MSCs for 10 days. C-MSCs and P-MSCs were isolated from the same donor. The cultures comprised of serum-free medium supplemented with 25 ng/ml each of SCF, TPO, Flt-3 L and IL-6. After 10 days cells were collected and analyzed for phenotype and functionality. RESULTS: C-MSCs and P-MSCs were found to be morphologically and phenotypically similar but exhibited differential ability to support ex vivo hematopoiesis. Cells expanded on P-MSCs showed higher percentage of primitive cells (CD34(+)CD38(−)), CFU (Colony forming unit) content and LTC-IC (Long term culture initiating cells) ability. CD34(+) cells expanded on P-MSCs also exhibited better in vitro adhesion to fibronectin and migration towards SDF-1α and enhanced NOD/SCID repopulation ability, as compared to those grown on C-MSCs. P-MSCs were found to be closer to BM-MSCs in their ability to expand HSCs. P-MSCs supported expansion of functionally superior HSCs by virtue of reduction in apoptosis of primitive HSCs, higher Wnt and Notch activity, HGF secretion and cell-cell contact. On the other hand, C-MSCs facilitated expansion of progenitors (CD34(+)CD38(+)) and differentiated (CD34(−)CD38(+)) cells by secretion of IL1-α, β, MCP-2, 3 and MIP-3α. CONCLUSIONS: P-MSCs were found to be better feeders for ex vivo maintenance of primitive HSCs with higher engraftment potential than the cells expanded with C-MSCs as feeders. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13287-015-0194-y) contains supplementary material, which is available to authorized users.